A double-blind trial of transfer factor vs placebo in multiple sclerosis patients. - Collins, R; Espinoza, L; Plank, C; Ebers, G; Rosenberg, R; Zabriskie, J (1978)
A double-blind trial of the effect of transfer factor on multiple sclerosis patients was carried out. In a series of fifty-six multiple sclerosis patients treated with monthly injections of either transfer factor or placebo for 1 year, no beneficial effect of transfer factor was noted. In addition, none of the immunological and serological parameters studied (measles migration inhibition, measles HI titre or CSF immunoglobulin) changed as a result of transfer factor therapy. Histocompatibility typing and CSF IgG/TP ratios were correlated with the disease activity. Of interest was the finding that the presence of the DW2 antigen, when unassociated with HLA-B7 antigen, appeared to correlate with the mildest form of disease activity.